Child to Parent Education in Prevention of Acute Diarrheal Diseases in Rural Schoolunder Rural Health Training Centre - Anirudha V Mutalik; Vaishali V Raje (Medsci Publications, 2018)
Introduction: Many children in middle and low income country like India die before they reach their fifth birthday most among them during the first year of life. Mother is the primary caregiver for the child in almost all societies across the world. Hence the health practices along with knowledge and attitude of the mothers directly implies on the health of the child. The aim of the study is to find out the change in level of knowledge, attitude and practice of parents after receiving health education from their school going children. Methodology: A pre structured & pretested questionnaires were used to assess the Knowledge, Attitude and Practice of children's at school & their mothers at home. The Pre and Post intervention scored are evaluated. Scoring system was developed & was compared among children's & their mothers. Results: Both Children and mothers of study group showed significant increase in knowledge, attitude and practice as compared to control group. Conclusion: An important determinant of child health is the knowledge of the Child's mother. Hence the health practices along with knowledge and attitude of the mothers directly implies on the health of the child.